PENGARUH TRAVEL MOTIVATION,UTILITARIAN VALUE, DAN OVERALL SATISFACTION TERHADAP RE-PATRONAGE INTETION - Clara Amelia Kuswandi; Siti Rahayu; Erna Andajani (Perpustakaan Universitas Surabaya, 2018)
This study is aimed to identify and analyze influence travel motivation, utilitarian value, and overall satisfaction toward re-patronage intention on previous research relevant infor-used at this time. Object taken is Mall in Yogyakarta.The data sources used in this study was primarily obtained from respondent using a set of questionnaires. Respondents in this study amounted to 150 people, the respondents who’ve been visited the mall in Yogayakarta in the last 1 year, and have a minimum educations of high school/vocational/equivalent. The sampling technique is a non-probability sampling with the kind of judgment sampling. Level measurement used are interval level. This study used method multiple regression analysis with using SPSS 22 for windows.The results of this study is indicate that travel motivation, utilitarian value, and overall satisfaction has a positive influence towards re-patronage intention.